The Impacts of Foreclosure on Collective Efficacy and Civic Engagement: Findings from Two Central California Communities - Weffer, Simón E. (Social justice, 2013)
The article discusses research findings on the effect of high foreclosure rates in California's Central San Joaquin Valley and civic engagement. Topics include the potential connection between collective efficacy and residential stability and its interruption by home foreclosures, statistical analyses of demographic indicators and survey responses regarding issues of social cohesion.